PENGARUH APLIKASI KOMPOS AMPAS KOPI TERHADAP PERUBAHAN SIFAT KIMIA ANDISOL NGABAB, KABUPATEN MALANG - Wenry Siahaan; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Application of spent coffee ground compost is expected to improve soil chemical properties of Andisol Ngabab which has low C-organic and N contents, very low P content, and moderate content of Na content. The purpose of this study was to explore the effect of application of Robusta spent coffee grounds compost application on soil chemical properties of an Andisol. This study used a completely randomized design with five treatments and three replications. The treatments tested were P0 (control, without application of spent coffee ground compost), P1 (50% dose of spent coffee ground compost aplication = 10 t ha-1), P2 (100% dose of spent coffee ground compost application = 20 t ha-1), P3 (150% dose of spent coffee ground compost application = 30 t ha-1), and P4 (200% dose of spent coffee ground compost application = 40 t ha-1). The results of this study showed that the application of spent coffee ground compost with a dose of 150%= 30 t ha-1 (P3) and dose of 200%= 40 t ha-1 (P4) on an Andisol of Ngabab significantly increased pH, organic-C, total-N, available-P, exchangeable-K (in 2, 6 and 8 weeks), exchangeable-Na, and CEC (in 4, 6 and 8 weeks) compared to control treatment or without application of spent coffee ground compost (P0).